STUDIES ON LENGTH FREQUENCY OF OILSARDINE AT CALICUT DURING 1970-71 to 73-74 - Rengaswamy, V S (Indian Journal of Fisheries, 2011)
Studies M Ca'Hcut on ~ge and growth of c-ilsallXEne Sardinella longicepshy means of length-frequency method indkated thalt the oilsardine aÂ·ttains thetotal length of 125-13q mm at the end of one year, 165-175 mm at the end oftwo years and 180-190 mm on comp~et~on of three yeÂ·a;rs. From ~he m01nthlyprogression of modes during different years, it c()uld be seen that the fishelry wasmainly suppoJ1ted by the O-year, l-yea.rand 2-yea1r oJ.a1sses. The Mudies alsolfevea